Perencanaan Arsitektur Enterprise Dengan Kerangka Kerja TOGAF (The Open Group Architecture Framework) - Latjuba Sofyana (PROZIMA (Productivity, Optimization and Manufacturing System Engineering), 2017)
PT Puma Logistic Indonesia is a company which dwelled in freight forwarder services. Services provided include export, import, domestic transportation, and warehousing. In carrying out its business activities, the company still use manual processes, such as using Microsoft office applications for bookkeeping and archiving. Manual data management will present a lot of risks, including simple errors in recording or data input. Not to mention the time that it takes relatively longer to access and to process information, and the shortade will affect the late information provided to the Head of Branch as well as the Director. Therefore, PT Puma Logistics Indonesia requires need information technology and system that could support and manage the company’s business process well. Based on above problems, PT Puma Logistic Indonesia need enterprise architecture planning which is ideal for their company vision and mission and also the company’s future development. Enterprise architecture planning in this research use TOGAF ADM framework which focused on architecture planning which produce steps of business architecture, information and technology development. The results of this study indicate that the enterprise architecture planning using TOGAF ADM can produce models of enterprise architecture (blueprint). The blueprint can be used as a guide in the procurement and development of IS / IT at PT. Puma Logistics Indonesia, including 13 business functions that have been adapted to business functions that will come in the business process architecture, 27 new entities in the data architecture, 4 application modules in architectural applications and the technology architecture in the form of the provision and upgrading hardware and software in PT. Puma Logistics Indonesia